Eksistensi Hukum Islam dalam Pembentukan Perundang-Undangan di Indonesia: Undang-Undang Perkawinan, Undang-Undang Zakat, Undang-Undang Haji, dan Kompilasi Hukum Islam (KHI) - Batara, A Muhammad; Rahman R, Abd.; Gassing, Qadir (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the existence of Islamic law in Indonesian legislation, focusing on the Marriage Law, Zakat Law, Hajj Law, and the Compilation of Islamic Law (KHI). Using a library research method, the study aims to understand how Islamic law has been recognized as an integral part of the national legal system and its implications for nation-building. The findings reveal that Islamic law is not only practiced within society but also institutionalized in positive law: the Marriage Law No. 1/1974 as a codification of Islamic family law, Zakat Law No. 23/2011 as both a religious obligation and a social welfare instrument, Hajj Law No. 13/2008 (later Law No. 8/2019) ensuring the administration of pilgrimage in accordance with sharia, and KHI as a unification of Islamic family law applied in Religious Courts. In conclusion, Islamic law significantly contributes to the development of Indonesia’s legal system by strengthening moral values, ethics, and justice, while highlighting the need for harmonization between Islamic law and the national legal framework based on Pancasila and the 1945 Constitution.